Canas-Segovia V. United States immigration and naturalization service brief amicus curiae of the office of the united nations high commissioner for refugees - Goodwin-Gill, G; Timberlake, S; Steinhardt, R (1990)
In April 1990, the United States Court of Appeals for the Ninth Circuit gave judgment in Canas-Stgovia v. Immigration and Naturalization Service, a case involving applications for asylum by two brothers, both citizens of El Salvador and Jehovah's Witnesses. The Court upheld the appeal, and ruled that the appellants qualified for asylum in the United States. As it had done in three previous cases, the Office of the United Nations High Commissioner for Refugees submitted an amicus curiae brief in support of appellants. This brief examines the law and practice relating to conscientious objection, and considers how and in which circumstances those who refuse to do military service can be considered as refugees under the 1951 Convention/1967 Protocol. It shows that under the well-founded fear of persecution standard, the likelihood of punishment under a law of universal or general application does not itself rule out the possibility of persecution within the meaning of the Convention; that an 'intent to persecute' on the part of a government or other State authority is not a necessary precondition for the existence of a well-found fear of persecution; and that UNHCR has consistently adopted these positions, as shown particularly by the relevant provisions of the UNHCR Handbook on Procedurts and Crittnafor Determining Rifugtt Status. The brief also examines the international legal standing of the right to conscientious objection, considered on its own merits in the human rights context, from the perspective of State practice and that of international and regional organizations; it refers to significant developments in various United Nations fora. The brief argues that the Board of Immigration Appeals appears to have interpreted the petitioners' claims as based solely on a well-founded fear of religious persecution. But, regardless of the precise characterization of the applicant's motives, the conscientious refusal to bear arms inevitably places the individual in political opposition to his or her government, in a situation of conflicting duties that should be resolved in accordance with international standards of reasonableness and proportionality. Finally, the brief suggests a framework of standards within which the refugee status of conscientious objectors may be determined, taking account of the special value attributed to the individual's right to freedom of conscience and its relationship to competing interests of State and community. © 1990 Oxford University Press.